2015
DOI: 10.1590/s1517-707620150003.0057
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen dopedTiO2photoactive in visible light

Abstract: In this research TiO 2 modified with nitrogen has been prepared. The synthesis method used was sol gel from the hydrolysis of titanium tetrabutoxide with urea solution, combined with a low temperature treatment at atmospheric pressure. The theoretical mole ratio N/Ti was equal to 0.5 and the theoretical mole ratio HNO3/TiO 2 was equal to 0.5. The solid obtained was calcined at different temperatures in static air with high heating rate and residence time of 1 hour. The samples were characterized by X-ray diffr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…It was clearly seen that a single phase of anatase structure was obtained for all synthesis conditions. As reaction time increases, the crystallite size of N-doped TiO 2 nanopowder increased [12]. The influence of N doping on the particle size of the TiO 2 crystal was studied.…”
Section: Resultsmentioning
confidence: 99%
“…It was clearly seen that a single phase of anatase structure was obtained for all synthesis conditions. As reaction time increases, the crystallite size of N-doped TiO 2 nanopowder increased [12]. The influence of N doping on the particle size of the TiO 2 crystal was studied.…”
Section: Resultsmentioning
confidence: 99%
“…Due to this, the antimicrobial activity assessment has been widely performed to verify the effectiveness of degradations processes, such as ozonation (Venancio et al 2018;Serna-Galvis et al 2020;Venancio et al 2020). Also, studies with B. subtilis and E. coli reported EC 50 in μg L À1 levels for FQs (Pérez et al 2015;De Oliveira et al 2017), which was the same magnitude those observed in the present one (i.e., 1.1 μg L À1 (2.9 nmol) and 3.6 μg L À1 (9.6 nmol) for B. subtilis and E. coli, respectively). It is also important to highlight that non-interference was observed in the degradation process since the control response curve was like the untreated sample (t ¼ 0 min) (Figure 3).…”
Section: Residual Antimicrobial Activitymentioning
confidence: 99%
“…After the sun's rays fall on this material, active oxygen is generated, which in turn purifies water from pollutants, bacteria, fungi, germs, organic materials, as well as toxic elements such as arsenic As and Chromium Cr [1][2][3]. Titanium was first discovered in 1971 by an English chemist and geologist William Gregor And years later, titanium dioxide TiO 2 was manufactured for use as a whitening ingredient used in toothpastes, a multifaceted compound used as a strong photocatalyst capable of breaking any organic compound if exposed to the sun [4][5][6][7][8][9][10][11][12][13][14][15], and therefore can be used in cleaning and bleaching fabrics and purifying water / waste water and air [16] and in many other industrial applications such as the iron, electronics and chemicals industry, all the way to the manufacture of cosmetics, batteries and solar cells [17] and hydrogen production because of its important physical and chemical properties. It has chemical stability and is chemically non-toxic [2,3] and a high static permittivity, and is characterized by an Eg energy gap ranging between 3.04-3.46 eV [18], as it has A high resistivity estimated at 10 12 Ω.cm at a temperature of 25C°.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, we prepared samples of leaded titanium dioxide in different proportions, Pb:TiO 2 , and then we crushed these samples separately, sieved them and calcined them from 0 C° to 200 C° to remove moisture and used X-ray diffraction device (XRD) in order to study the properties The structural properties of these samples in order to improve the physical properties and expand the effectiveness and areas of use of titanium dioxide after many researchers have doped it with different chemical elements and compounds using each of the XRD, SEM, DRS, EDS, FT-IR devices and others, which showed the displacement of the radiation absorption field from ultraviolet rays to include raising the efficiency of absorption of these rays as well as light rays, narrowing the band gap, and thus increasing the photocatalytic property [23], electrical conductance and other electronic, physical and microscopic properties [2,4,7,10,[12][13][14][15]18,19,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%